Automated Rain-Sensing Window Closure Redefines Home Comfort: Penutupan Jendela Sensor Hujan Otomatis Mendefinisikan Kembali Kenyamanan Rumah - Al A’roof , Asegaf; Iswanto, Iswanto (Universitas Muhammadiyah Sidoarjo, 2024)
The research on the design and development of an automatic window covering system using a rain sensor presents significant findings and implications. Through the integration of innovative technologies like the rain sensor and direct current motor GW4632-370, the system effectively responds to weather changes by automatically closing windows when it rains, thereby preventing water ingress into indoor spaces. The study's findings underscore the feasibility and practicality of implementing such systems to enhance convenience and protect interior spaces from adverse weather conditions. Moreover, the successful creation of a 3D window frame design and the establishment of the electrical current circuit demonstrate the potential for broader applications in smart home and office automation. However, further research is warranted to optimize the system's efficiency, explore alternative power sources, and assess its long-term durability and reliability in real-world settings. Highlight: Integration of rain sensor: Enables automatic window closure during rain. Utilization of smart home technology: Enhances convenience and weather protection. Development of electrical circuit: Facilitates seamless operation and energy efficiency. Keywoard: Automatic window covering, Rain sensor, Smart home technology, Electrical circuit, Weather-responsive system